2019
DOI: 10.1161/circulationaha.118.034549
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Calmodulin-Kinase II Activation Drives Disease Progression in Mutation-Specific Hypertrophic Cardiomyopathy

Abstract: Background: Although the genetic causes of hypertrophic cardiomyopathy (HCM) are widely recognized, considerable lag in the development of targeted therapeutics has limited interventions to symptom palliation. This is in part attributable to an incomplete understanding of how point mutations trigger pathogenic remodeling. As a further complication, similar mutations within sarcomeric genes can result in differential disease severity, highlighting the need to understand the mechanism of progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…In addition, we performed prespecified pathway analysis for calcium-handling genes, NMD genes, and hypertrophy-associated genes. Further supporting an absence of calcium mishandling in the early developmental stage, we found no significantly dysregulated calcium-handling genes in either heterozygous or homozygous models ( Figure 5C), including ATPA2A (Serca2) and CAMK2D, both of which are dysregulated in HCM patient cardiac tissue and in mouse models of HCM (28,30). We also found no significant differential expression of NMD genes in MYBPC3 mutation lines, including in frameshift mutation lines (in which NMD degrades mutant mRNA transcripts) versus promoter deletion or start site mutation lines (in which mRNA loss of function occurs without NMD).…”
Section: Resultssupporting
confidence: 66%
“…In addition, we performed prespecified pathway analysis for calcium-handling genes, NMD genes, and hypertrophy-associated genes. Further supporting an absence of calcium mishandling in the early developmental stage, we found no significantly dysregulated calcium-handling genes in either heterozygous or homozygous models ( Figure 5C), including ATPA2A (Serca2) and CAMK2D, both of which are dysregulated in HCM patient cardiac tissue and in mouse models of HCM (28,30). We also found no significant differential expression of NMD genes in MYBPC3 mutation lines, including in frameshift mutation lines (in which NMD degrades mutant mRNA transcripts) versus promoter deletion or start site mutation lines (in which mRNA loss of function occurs without NMD).…”
Section: Resultssupporting
confidence: 66%
“…Changes in CaMKII signaling have been previously reported in human and mouse models of HCM (Helms et al, 2016;Lehman et al, 2019). We, therefore, also assessed the levels of expression and phosphorylation of CaMKII in our mice.…”
Section: Phosphorylation Of Cardiac Myofilament Proteins Is Not Altermentioning
confidence: 94%
“…We determined cardiac function (using both standard echocardiographic parameters and speckle strain measurements), histology, and myofilament function. We also established levels of Ca 2+ /calmodulindependent protein kinase II (CaMKII) phosphorylation, which has been reported to be a key signaling pathway in human HCM (Helms et al, 2016) and in mouse HCM models (Lehman et al, 2019). We observed that KO of PLN in hearts of cTnT-R92Q mice resulted in decreased CaMKII phosphorylation and a prevention of the development of the HCM phenotype, although the increase in myofilament Ca 2+ sensitivity was preserved.…”
mentioning
confidence: 95%
“…The situation is compounded further when considering that hundreds of different mutations occur in a myriad of proteins, each presumably resulting in distinct molecular and patient phenotypes. As one example, two different mutations that affect the same residue in troponin T (R92L and R92W) lead to divergent phenotypes [10]. However, the converse is also often true and presents an equally challenging paradox: How can different mutations in different proteins ultimately activate similar pathways that lead to the classical descriptions of HCM or DCM?…”
mentioning
confidence: 99%
“…Because an increase in Ca 2+ sensitivity of tension can account for slowed relaxation as well as the preserved (or even hyper-contractile) systolic function often seen in HCM patients, the hypothesis is attractive both for its simplicity and because it is suggestive of therapeutic remedies that target Ca 2+ sensitivity [1,2]. Nonetheless such generalizations are not universal [3,7,10] and are likely to be over-simplifications that lack the sensitivity or specificity necessary for predicting individual patient disease burden. Clearly, despite the enormous progress made in identifying the root genetic causes of cardiomyopathies, there is still much more to learn regarding if, when, and how a given mutation will impact patient lives.…”
mentioning
confidence: 99%